Pharmacist Recommendations for Non-Infectious Diarrhea Self-Medication: A Study in Padang, Indonesia - Hansen Nasif; Dwisari Dillasamola; Wira Sanjaya; Dian Ayu Juwita (Journal of Public Health and Pharmacy, 2025)
Introduction: Diarrhea is a condition where a person defecates with a soft or liquid stool consistency or even just water which can be accompanied by blood or foam with a frequency that is more frequent than usual in a day. Self-medication is an action taken by someone to treat themselves by recognizing the symptoms and illnesses felt, usually minor illnesses, then choosing drugs according to their wishes without going through a doctor's prescription. Methods: A descriptive study with cross-sectional approach to determine the recommended choice of diarrhea drugs without symptoms of infection for self-medication from pharmacies in Padang City, West Sumatra, Indonesia. Data were collected through proportional random sampling using the Slovin formula. From a total of 247 pharmacies in Padang City, data was collected from 38 pharmacies that had been proportioned in 11 sub-districts in Padang City. Participants in this study were pharmacists on duty at the pharmacy. Data were collected through structured interviews recorded by pharmacists in pharmacies with a single question, what drug do you give for self-medication to adult patients with mild diarrhea without symptoms of infection. Results: Drug recommendations from pharmacist in Padang City pharmacies are attapulgite, kaolin-pectin, activated carbon, loperamide, Oral Re-hydration Formula (ORS), zinc supplements, probiotics, and antacids. The drug recommendations given are in the form of single therapy and combination therapy. Assessment of recommendations that are said to be appropriate refers to the recommendations of Dipiro (2020), namely the provision of a single absorbent or absorbent plus ORS. The results of appropriate recommendations were obtained at 44.74% and those that were not appropriate were obtained at 55.26%. There is no statistically significant evidence to suggest a relationship between the education level of pharmacist and appropriate of the answer (p>0.05). Conclusion: There are still many mistakes made by pharmacists in recommending diarrhea drugs without symptoms of infection for self-medication in pharmacies.